Descriptive markup languages and the development of digital humanities (Libellarium: journal for research in the field of information and related sciences, 2012)
The paper discusses the role of descriptive markup languages in the development of digital humanities, a new research discipline that is part of social sciences and humanities, which focuses on the use of computers in research. A chronological review of the development of digital humanities, and then descriptive markup languages is exposed, through several developmental stages. It is shown that the development of digital humanities since the mid-1980s and the appearance of SGML, markup language that was the foundation of TEI, a key standard for the encoding and exchange of humanities texts in the digital environment, is inseparable from the development of markup languages. Special attention is dedicated to the presentation of the Text Encoding Initiative – TEI development, a key organization that developed the titled standard, both from organizational and markup perspectives. By this time, TEI standard is published in five versions, and during 2000s SGML is replaced by XML markup language.
Keywords: markup languages; digital humanities; text encoding; TEI; SGML; XML